Pemantauan Kualitas Air Sungai di Kabupaten Tasikmalaya - Meylani, Vita; Mutiara, Frista; Muslim, Farhan Fuadi (Mahesa Research Center, 2024)
Monitoring river water quality in Tasikmalaya Regency is an important indicator in determining IKLH (Environmental Quality Index) and the function of water for people's lives. This research was conducted to analyze the results of observations testing physical parameters (color and odor, turbidity, TDS and temperature), chemical (pH and DO/dissolved oxygen) and microbiology (total Coliform and Escherichia coli) taken from 9 river locations in the Regency Tasikmalaya using grab sampling using a descriptive qualitative approach and purposive sampling techniques. The results show that the water quality of 7 of the 9 location points still meets the water quality standards referred to in Appendix IV Government Regulation Number 22 of 2021 (Physical and Chemical Parameters) and Minister of Health Regulation Number 02 of 2023 (Microbiological Parameters). The parameters observed were odor and color with an average of odorless and 159.75 mg/L, turbidity with an average of 61.87 NTU, TDS with an average of 410.58 mg/L, temperature with an average of 27.83, pH with an average of 8.13, Dissolved Oxygen/DO with an average of 6.52 mg/L, Total Coliform with an average of 1079.88 MPN/100 mL, and Escherichia coli with an average of 1080.67 MPN/100 mL. The parameters that mostly exceed water quality standards on average at all sampling points are color, turbidity, DO (Dissolved Oxygen), TDS (Total Dissolved Solid), Total Coliform, and Escherichia coli.